ナンキョク ミズホ コウゲン ジョウ ノ シャメン カッコウ フウ ノ ランリュウ ダイ1カイ ナンキョク キスイケン シンポジウム - 小林, 俊一; コバヤシ, シュンイチ; 石田, 完; イシダ, タモツ; KOBAYASHI, Shun'ichi; ISHIDA, Tamotsu (国立極地研究所, 1979)
P(論文) 超音波風速計による斜面滑降風(katabatic wind)の乱流特性が調べられた.観測地点は,みずほ基地の雪原上とやまと裸氷原上の2点であり,前者は,定常的な斜面滑降風域,後者は斜面滑降風のハイドロリックシャンプ(hydraulic jump)域として特徴づけられる.2つの地域の乱流特性の差は,自己相関係数から計算した特性時間スケールとパワースペクトルに著しく表れた. Wind turbulence was observed, using sonic anemometers, on a snow surface at Mizuho Station (2230 m above sea level, Lat. 70°41.9'S, Long. 44°19.9'E) and on a bare ice field near the Yamato Mountains (1700 m above sea level, Lat. 71°18'S, Long. 35゜40'E) in the Mizuho Plateau in 1973 by the party of the 14th Japanese Antarctic Research Expedition (JARE-14). Observations revealed, as to katabatic winds blowing above the two places, that the one above the latter is characterized by the presence of a hydraulic jump generated by nunataks there, resulting in a stronger turbulence than the one above the former which is stationary. Hence, a comparison is made in this paper between characteristics of turbulence and a hydraulic jump in a katabatic wind departmental bulletin paper